Peran Budaya Organisasi pada Lembaga Pendidikan Islam - Tarmizi Tahir; Nasrudin Harahap; Nurul Hidayati Murtafiah (Journal on Education, 2023)
This study means to look at how to foster authoritative culture in an association or in instructive foundations for the objectives and goals to be accomplished. This study utilizes a subjective examination approach. Subjective examination is an exploration method that involves enlightening information as composed or verbally expressed words from individuals and entertainers who can hurt. The outcomes showed that hierarchical culture is a paste, unifier, personality, picture, brand, trigger, conviction, esteem, standard of conduct that is acknowledged and associated in a kite way as framing the qualities of Islamic instructive foundations in managing outer difficulties and inside reconciliation, and is a worth framework that is accepted and can be learned, can be applied and grown ceaselessly, and authoritative culture is a typical viewpoint for a great many people towards Islamic instructive organizations.